Tradisi Mabbaca Doang Sebagai Warisan Budaya di Desa Leppangang Kabupaten Pinrang - Alvira Damayanti; Muh. Said; Rusdi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine: 1) An overview of the implementation of the Mabbaca Doang tradition as a cultural heritage in Leppangang Village, Pinrang Regency. 2) The noble values ​​contained in the Mabbaca Doang tradition include religious, social, cultural, and educational values. 3) Strategies for preserving the Mabbaca Doang tradition to ensure its relevance and sustainability amidst the current of modernization. This study uses a qualitative approach with a phenomenon-based approach through observation, interviews, and documentation methods. The results show: 1) The Mabbaca Doang tradition is carried out at various important events such as celebrations, harvests, housewarmings, the Hajj pilgrimage, and deaths, with ritual stages involving religious leaders, traditional figures, and active community participation. 2) This tradition contains religious values ​​in the form of strengthening faith and gratitude to God, social values ​​in the form of togetherness and solidarity, cultural values ​​in the form of local Bugis identity symbols of traditional food, and educational values ​​in the form of learning manners and prayers for the younger generation. 3) The preservation strategy is carried out through the involvement of the younger generation, as well as the use of digital media as a means of documentation and education. Overall, this study shows that the Mabbaca Doang tradition deserves to be considered a Cultural Heritage that needs to be systematically and sustainably preserved to strengthen the cultural identity of the Bugis Pinrang community.